Answer:
= (72 - 225d - (55/4)d^2) / (72d(18 + d))
Explanation:
To simplify the expression:
(72 - ((18 + d)^2)/144 * 4400)/(4(18 + d) * d)
First, let's simplify the numerator:
(72 - ((18 + d)^2)/144 * 4400) = (72 - ((18 + d)^2) * 4400/144)
Next, let's simplify the denominator:
4(18 + d) * d = 4d(18 + d)
Now we can rewrite the expression as:
(72 - ((18 + d)^2) * 4400/144) / (4d(18 + d))
To further simplify, we can calculate the squares and perform the arithmetic operations:
(72 - (18 + d)^2 * 4400/144) / (4d(18 + d))
= (72 - (18 + d)^2 * 4400/144) / (72d(18 + d))
= (72 - (18 + d)^2 * 4400/144) / (72d(18 + d))
= (72 - (18 + d)^2 * 4400/144) / (72d(18 + d))
= (72 - (324 + 36d + d^2) * 4400/144) / (72d(18 + d))
= (72 - (32400 + 3960d + 110d^2)/144) / (72d(18 + d))
= (72 - 225d - (55/4)d^2) / (72d(18 + d))